Reduction of water cost for an existing wind-energy-based desalination scheme: A preliminary configuration. (15th January 2019) - Rosales-Asensio, Enrique; Borge-Diez, David; Pérez-Hoyos, Ana; Colmenar-Santos, Antonio
Abstract: One possible contender to replace conventional reverse osmosis schemes is an energy solution where inexhaustible resources work together with a reverse osmosis plant. Based on the experience of an existing wind-powered desalination scheme run for more than 15 years by Soslaires Canarias S.L., the final objective of this paper is to propose improvements to the scheme so as to achieve a reduction in the cost of water (through restrained capital expenses) for the sake of greater feasibility and efficiency. The cost of the scheme is evaluated assuming a combined use of a reverse osmosis desalination plant and wind energy, using, for this purpose, the (exclusive) information provided by the industrial partner. Results showed that by carrying out the actions suggested in this paper, this scheme would be able to reduce its cost of water (COW) by about 0.022 EUR per cubic meter for the current LCOE of wind turbine technology in the study area (about 6 c€/kWh for the southeast of the island of Gran Canaria, Spain). This would mean that with an additional total capital investment cost of 196 000 € (from the current scheme of Soslaires Canarias S.L.), and supposing an average membrane life expectancy of 10 years for the current state-of-the-art membranes, a net present value of 74 360.95 €, a profitability index of 1.3794, and a 224.4881% internal rate of return would be achieved. Graphical abstract: Typical cost structure for RO seawater desalination.Image 1 Highlights: Several configurations of desalination plants based RES have been simulated. Cost of water has been considered as the central element of the evaluation. In case of carrying out the actions suggested COW would be reduced.